2021
DOI: 10.1177/02692155211061221
|View full text |Cite
|
Sign up to set email alerts
|

Breathing exercises versus strength exercises through telerehabilitation in coronavirus disease 2019 patients in the acute phase: A randomized controlled trial

Abstract: Objective To compare the effectiveness of two different exercise-based programs through telerehabilitation in patients with coronavirus disease 2019. Design Randomized, controlled, parallel, double-blinded, three-arm clinical trial. Setting Patients’ homes through telerehabilitation devices. Subjects Subjects with coronavirus disease 2019 in the acute phase. Interventions Subjects were divided into three groups: breathing exercises group, strength exercises group or no treatment/control group. Main measures We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
80
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(86 citation statements)
references
References 35 publications
2
80
1
3
Order By: Relevance
“…Of these, six randomised controlled trials (reported across seven articles) were included in this review. 25 , 26 , 27 , 28 , 29 , 30 , 31 The 14 studies that did not meet the eligibility criteria were excluded due to ineligible study design (n = 10), ineligible population (n = 3) and ineligible comparator (n = 1) ( Figure 1 ). Twenty-five ongoing studies were also identified: three on the databases and 22 on the ClinicalTrials.gov registry website; see Appendix 2 on the eAddenda for a summary of the ongoing trials.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, six randomised controlled trials (reported across seven articles) were included in this review. 25 , 26 , 27 , 28 , 29 , 30 , 31 The 14 studies that did not meet the eligibility criteria were excluded due to ineligible study design (n = 10), ineligible population (n = 3) and ineligible comparator (n = 1) ( Figure 1 ). Twenty-five ongoing studies were also identified: three on the databases and 22 on the ClinicalTrials.gov registry website; see Appendix 2 on the eAddenda for a summary of the ongoing trials.…”
Section: Resultsmentioning
confidence: 99%
“…Rodriguez-Blanco et al contributed two of the included trials. 25 , 26 In their trial published in 2021, a 7-day strength and resistance exercise program was compared with no intervention. 25 The experimental group received instructions on how to perform the exercises through a website and a daily text message was sent asking about the exercises and as a follow-up method to improve adherence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations